Nanotoxicity - An electrochemist's perspective - Batchelor-McAuley, C; Tschulik, K; Compton, R (2013)
This article highlights the fundamental role of mass-transport for interfacial reactions. First, the dissolution of particulate CaCO3 is discussed demonstrating how the dimensions of the dissolving particle can 'switch' the reaction mechanism from being diffusion to surface controlled. Second, the influence of mass-transoprt on electrochemical reactions is considered, specifically considering how electrode modification can alter the observed voltammetric response in the absence of changing the electrochemical mechanism or the rate of electron transfer. Finally, these observations on the chemically controlling role of mass-transport are concluded by considering nanoparticle toxicity and how 'size effects' may be exhibited even in the absence of altered thermodynamics or interfacial kinetics of the reactions involved.